Analysis of Student Habits of Mind After the Implementation of Inquiry Based Learning With Levels of Inquiry - Sanjayanti, Arum (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In order to prepare teachers and next generation for twenty first century can act based on their higher order thinking skills, teacher, students need have relevant experience. In Biology instruction, it seems needed habits of higher order thinking in solving problem in processes such as inquiry based learning. Through inquiry, the students will be able to develop science and intellectual skills necessary to solve problem and find out the answer to fulfill their curiosity. A descriptive study was carried out to investigate students habits of mind after having experience in IBL in certain topics, among others were on Biodiversity topic. Habits of mind with 16 categories, meanwhile IBL with six levels of inquiry (discovery learning, interactive demonstration, inquiry lesson, inquiry lab, real world application and hypothetical inquiry). Qualitative method in this research was conducted with the use of questionnaire on Habits of mind and individual interview toward students. Research results show that students Habits of mind is in average category, the IBL can facilitate students higher order thinking experience, and most of the students agree to lengthen the implementation of the IBL for other Biology topics so as to be able to become good thinkers in near future. Key words: analysis, student’habit, inquiry based learning